2021
DOI: 10.3390/pathogens10050576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Study of Hand, Foot, and Mouth Disease in a Kindergarten-Based Setting in Bangkok, Thailand

Abstract: Hand, foot, and mouth disease (HFMD) is a contagious childhood illness and annually affects millions of children aged less than 5 years across the Asia–Pacific region. HFMD transmission mainly occurs through direct contact (person-to-person) and indirect contact with contaminated surfaces and objects. Therefore, public health measures to reduce the spread of HFMD in kindergartens and daycare centers are essential. Based on the guidelines by the Department of Disease Control, a school closure policy for HFMD ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
3
12
1
Order By: Relevance
“…Researchers proposed that unique amino acid substitutions of CV-A6 strains might lead to changes in virological characteristics such as antigenicity and had been emerged every 2 years to cause epidemics ( 20 ). As there were no samples tested EV-A71 positive, our result did not conform with some findings, where EV-A71 was with a large proportion ( 21 , 22 ). This may result from territorial differences, revealing the necessity of strengthening disease surveillance.…”
Section: Discussioncontrasting
confidence: 99%
“…Researchers proposed that unique amino acid substitutions of CV-A6 strains might lead to changes in virological characteristics such as antigenicity and had been emerged every 2 years to cause epidemics ( 20 ). As there were no samples tested EV-A71 positive, our result did not conform with some findings, where EV-A71 was with a large proportion ( 21 , 22 ). This may result from territorial differences, revealing the necessity of strengthening disease surveillance.…”
Section: Discussioncontrasting
confidence: 99%
“…We also found that children under 5 years are the main morbid population, accounting for 94.17% of all reported cases. The result was consistent with other research’s findings in other countries and China [ 1 , 6 , 46 , 50 ]. The low incidence of children over 5 years old maybe because they have had HFMD before, thereby protecting them and their peers from HFMD [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, the interrupted time series analysis results indicated that, after the introduction of the vaccine, the incidence of HFMD showed an upward trend, and increased faster than before in mainland China. The incidence of HFMD in Mainland China was 169.41 per 100,000 in 2018, which was only lower than the incidence in 2014 and 2016, higher than Thailand’s incidence rate of 102.51/100,000 [ 46 ] and Malaysia’s incidence rate of 138.6/100,000 [ 47 ]. So, the incidence of HFMD was still at a high level in mainland China in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis of Dingxi City with a high proportion of EC and SI also shows that there was a linear positive relationship between EC and SI. Other factors, such as gatherings of people [ 52 , 53 ] and levels of vaccine coverage [ 54 , 55 ] may also influence the relationship between EC and SI, which need further investigation in future studies. Furthermore, this may provide scientific evidence for health administrative departments to formulate HFMD prevention, control strategies, and the distribution of health resources when monitoring the patterns of EC.…”
Section: Discussionmentioning
confidence: 99%